Human chimera-type galectin-3: defining the critical tail length for high-affinity glycoprotein/cell surface binding and functional competition with galectin-1 in neuroblastoma cell growth regulation - Kopitz, Jürgen; Vértesy, Sabine; André, Sabine; Fiedler, Sabine; Schnölzer, Martina; Gabius, Hans-Joachim (Biochimie, 2014)
Many human proteins have a modular design with receptor and structural domains. Using adhesion/growth-regulatory galectin-3 as model, we describe an interdisciplinary strategy to define the functional significance of its tail established by nine non-triple helical collagen-like repeats (I-IX) and the N-terminal peptide. Genetic engineering with sophisticated mass spectrometric product analysis provided the tools for biotesting, i.e. eight protein variants with different degrees of tail truncation. Evidently,various aspects of galectin-3 activity (cis binding and cell bridging) are affected by tail shortening in a different manner. Thus, this combined approach reveals an unsuspected complexity of structure-function relationship, encouraging further application beyond this chimera-type galectin.